Restless Legs Syndrome in Parkinson's Disease Patients: Clinical Features Including Motor and Nonmotor Symptoms - You, Sooyeoun; Jeon, Soo Myeong; Do, So Young; Cho, Yong Won (Journal of clinical neurology (Seoul, Korea), 2019)
We investigated the frequency and clinical features of restless legs syndrome (RLS) in patients with Parkinson's disease (PD). This study included 74 PD patients. RLS was diagnosed in face-to-face assessments of all of the subjects based on diagnostic criteria of the International Restless Legs Syndrome Study Group revised in 2003. We analyzed the clinical features of PD patients with and without RLS and compared the data to idiopathic RLS. The frequency of RLS in the cohort was 21.6% ( =16). Two (12.5%) of the patients with RLS were not treated with dopaminergic drugs, while 14 (24.1%) of the 58 patients without RLS received treatment with dopaminergic drugs. Anxiety, depression, and quality of life (QoL) were significantly worst in patients with RLS. PD patients with RLS had significantly worse sleep quality ( =0.003) and worse scores on the cardiovascular subscale of the Scales for Outcomes in Parkinson's Disease for Autonomic Symptoms ( =0.031) compared to those without RLS. In the group of PD patients with RLS, RLS preceding PD onset was related to a lower Hoehn and Yahr stage. We found that the frequency of RLS in the present patients with PD was higher than that in our previous study of a general population of RLS subjects. Compared to the PD patients without RLS, the present PD patients with RLS suffered from worse sleep quality and QoL, depression, anxiety, and autonomic disturbances, especially those with cardiovascular problems.